2006
DOI: 10.2340/00015555-0128
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Gel 0.3% Does Not Relieve Pain During Topical Photodynamic Therapy: A Randomized, Double-blind, Placebo-controlled Study

Abstract: There is a demand for pain relief during photodynamic therapy. We therefore investigated the efficacy and side-effects of topical morphine gel 0.3% for pain relief during topical photodynamic therapy in a randomized, double-blind, placebo-controlled study. The study involved 28 patients with actinic keratoses or basal cell carcinomas. Each patient was treated with photodynamic therapy after superficial curettage of 2 treatment areas that were randomized to morphine gel or placebo gel. The gels were applied 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 20 publications
2
45
0
2
Order By: Relevance
“…The application of local anaesthetics like lidocaine/prilocaine substances prior to illumination is generally not recommended. As previously shown also application of morphine 0.3% gel 15 min prior to illumination did not result in a significant reduction of pain as compared to a placebo gel [46].…”
Section: Practical Application Tolerability and Side Effectssupporting
confidence: 54%
“…The application of local anaesthetics like lidocaine/prilocaine substances prior to illumination is generally not recommended. As previously shown also application of morphine 0.3% gel 15 min prior to illumination did not result in a significant reduction of pain as compared to a placebo gel [46].…”
Section: Practical Application Tolerability and Side Effectssupporting
confidence: 54%
“…Several studies have been conducted to examine the various topical pain relief methods during PDT, without convincing results (26)(27)(28)(29)(30). In a recent study by Tyrell et al (31), the use of air cooling as pain relief resulted in less protoporphyrin IX photobleaching and consequently in reduced efficacy.…”
Section: Discussionmentioning
confidence: 96%
“…12,14e16 It has previously been reported that morphine gel 13 and tetracaine gel 24 can be inadequate analgesia for PDT patients.…”
Section: Discussionmentioning
confidence: 99%